The mediating role of online learning motivation in the influence of service quality, social media usage, and pedagogical teaching competence of teachers on student learning satisfaction - Ida Bagus Putu Puja (Cogent Social Sciences, 2024)
This study examines the landscape of technology-integrated learning in Indonesian education, focusing on the crucial role of online learning, despite technological advancements and social media utilization. The investigation scrutinized the mediating function of online learning motivation in the nexus between service quality, social media engagement, pedagogical competence of educators, and student learning satisfaction. Employing a quantitative approach, specifically an ex-post facto design, the research included 345 respondents from 28 vocational high schools in Gianyar, Indonesia, encompassing both public and private institutions. Partial Least Squares Structural Equation Modelling (PLS-SEM) analysis indicated a significant link between educational service quality and online learning motivation (0.367). Teachers’ pedagogical competence also has a noteworthy influence on online learning motivation (0.003). Additionally, both educational service quality (0.301) and social media use (0.031) significantly affected learning satisfaction. In conclusion, this study highlights that higher-quality educational services are positively associated with increased online learning motivation. However, increased use of social media does not necessarily result in increased online learning motivation. Similarly, improvements in teachers’ pedagogical skills do not immediately translate into increased online learning motivation.